The genus Stenodynerus de Saussure, 1863 (Hymenoptera: Vespidae: Eumeninae) from China: a new species, new records, and key to the species - Zeng, Xin; Chen, Bin; Li, Ting-Jing (Zootaxa, 2024)
The fauna of the genus Stenodynerus de Saussure, 1863 of China is supplemented with one new species and six new records, for a total of 30 recorded species. The new species, S. tongrenensis Zeng, Chen & Li, sp. nov., is described and illustrated in detail from Guizhou (China). The six following species are newly recorded from China: S. coreanus (Tsuneki, 1970), S. difficilis (Morawitz, 1867), S. kaszabi Giordani Soika, 1976, S. punctifrons (Thomson, 1874), S. steckianus (von Schulthess, 1897), and S. trotzinai (Morawitz, 1895). An updated key to the Chinese species of Stenodynerus is given.